Chalk Yeasts Cause Gluten-Free Bread Spoilage - Michela Pellegrini; Lucilla Iacumin; Francesca Coppola; Federica Barbieri; Chiara Montanari; Fausto Gardini; Giuseppe Comi (Microorganisms, 2025)
Four different yeast strains were isolated from industrial gluten-free bread (GFB) purchased from a local supermarket. These strains, including Hyphopichia burtonii, Wickerhamomyces anomalus, Saccharomycopsis fibuligera, and Cyberlindnera fabianii, are responsible for spoilage, which consists of white powdery and filamentous colonies due to the fragmentation of hyphae into short-length fragments (dust-type spots) that is typical of the spoilage produced by chalk yeasts. The isolated strains were identified using genomic analysis. Among them, C. fabianii was also isolated, which is a rare ascomycetous opportunistic yeast species with low virulence attributes, uncommonly implicated in bread spoilage. The yeast growth was studied in vitro on Malt Extract Agar (MEA) at two temperatures (20 and 25 °C) and at different Aws (from 0.99 to 0.90). It was inferred that the temperature did not influence the growth. On the contrary, different Aws reduced the growth, but all the yeast strains could grow until a minimum Aw of about 0.90. Different preservatives (ethanol, hop extract, and sorbic and propionic acids) were used to prevent the growth. In MEA, the growth was reduced but not inhibited. In addition, the vapor-phase antimicrobial activity of different preservatives such as ethanol and hop extract was studied in MEA. Both preservatives completely inhibited the yeast growth either at 20 or at 25 °C. Both preservatives were found in GFB slices. Contrary to hop extract, 2% (v/w) ethanol completely inhibited all the strains. The spoilage was also confirmed by the presence of various compounds typically present in yeasts, derived from sugar fermentation and amino acid degradation. These compounds included alcohols, ketones, organic acids, and esters, and they were identified at higher concentrations in the spoiled samples than in the unspoiled samples. The concentration of acetic acid was low only in the spoiled samples, as this compound was consumed by yeasts, which are predominately present in the spoiled samples, to produce acetate esters.